Augmented Reality Learning Media Design Based on Android Smartphones for Computer Network Subjects in Vocational Schools - Taufik, Ashbul; Alamsyah, Nur; Saputra, Andika (PT ARRUS Intelektual Indonesia, 2024)
The aim of this research is to produce an Android smartphone-based augmented reality learning media based on computer network hardware. The specific aim is to describe the results of the application model design, application functionality, and application feasibility. The approach method used in this research is research and development. Development stages include research, data collection, planning, product draft development, product validation, revision of product validation results, field trials, revision of field trial results, final product refinement, and dissemination. This research has been successfully carried out, and the results obtained in this research show that all respondents' results are in the feasible category. So it can be concluded that learning computer network hardware material using augmented reality based on Android smartphones is suitable for application in computer network subjects.